THE HIGHER EDUCATION FINANCING BASED ON ISLAMIC SHARIAH: AN UNCONVENTIONAL APPROACH OF STUDENT LOAN - Pfordten, Nor Effuandy; Ali, Md. Jafor; Sabli, Norhaila Bt.; Uddin, Md. Kamal; Bhuiyan, Abul Bashar (American Economic & Social Review, 2021)
Quality Higher Education transforms human life into meaningful human resources. Moreover, it brings qualitative changes in humankind and socioeconomic development with the help of extended knowledge and higher skills. But, most of the traditional student loan mechanisms are based on interest (riba) therefore, many devout Muslims are struggling with traditional student financing, as interest (riba) is impermissible in Islamic shariah. This study aims to analyze student financing concepts based on shariah perspective and to evaluate the shariah issues that are associated to its application. The present qualitative study adopts mostly relied primary and secondary sources of Islamic shariah such as Quran, Hadith, Islamic Jurisprudence, and Islamic scholars’ views. The deliberations evolve at reviewing on the shariah concept of Qard-al-hassan, Qard-bil-ujrah, waqf (Islamic trust bank), and takaful. Finally, the present study highlights that the higher education financing based on the shariah concept could also be generalized into education financing that would be interest(riba) free and acceptable to the Muslim community at large.